The effect of calcium and vitamin D supplementation on body composition and weight reduction: a randomized, triple-blind, controlled trial - Rajaie, Hamide; Bellissimo, Nick; Keshavarzi, Sareh Keshavarzic; Faghih, Shiva (Progress in Nutrition, 2018)
Background and aims: Multiple studies have suggested that calcium can supplement diet-induced weight loss, and that vitamin D is the most important regulator of intestinal calcium absorption. The aim of this study was to compare the effects of calcium, vitamin D, and calcium and vitamin D (Ca + Vit D) supplementation on body composition and weight loss in overweight or obese women. Methods: In this triple-blind, randomized, parallel, placebo-controlled trial, 100 overweight or obese premenopausal women were randomly allocated to one of the following 4 treatment groups for 8 weeks: 1) calcium supplement (2 tablets per day, each containing 500 mg calcium carbonate), 2) vitamin D supplement (2 tablets per day, each containing 200 IU vitamin D3), 3) Ca + Vit D supplement (2 tablets per day, each containing 500 mg calcium carbonate plus 200 IU vitamin D3), or 4) placebo (2 tablets per day, containing micro-cellulose). All groups received a2093 kJ (500 kcal) energy-restricted diet. Anthropometric measurements, body composition and serum vitamin D levels were measured before and after the intervention. Physical activity and 24 h dietary records were taken at baseline, week 4 and week 8 of the intervention. Results: There were significant reductions in body weight, body mass index, waist circumference (p<0.001 for all), and body fat mass (p<0.05) in all treatment groups after the intervention. However, the results were not significantly different among the four treatments groups after adjusting for potential covariates. Conclusion: Calcium, vitamin D, or Ca + Vit D supplements had no effect on body composition and weight loss even in low vitamin D and calcium consumers.